2015
DOI: 10.1159/000368907
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Peduncle Tumor Ablated by Novel 3-mm Laser Tip

Abstract: Background/Objective: Decisions to use open surgery or radiotherapy in pediatric patients with familial neoplastic syndromes must consider not only the symptomatic benefits of treatment, but also future limitations these treatments may impose. Specifically, open surgical resection of noncurable tumors may preclude or encumber future lesion resections, while radiotherapy has detrimental effects on pediatric cognitive development and increases the risk of future malignancy development. We provide the first repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…One patient previously treated for OPG in the first year of life and for aqueductal stenosis at the age of 7 developed a PA of the right frontal lobe at the age of 11 and underwent thermal ablation (LITT procedure) of this lesion. Although the long-term effects of laser ablation in patients with NF1 are not yet known, this technique is more precise, less invasive, does not involve ionizing radiations in terms of volume of tissue ablation compared to other methods, and allows complete resection, avoiding collateral damage [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…One patient previously treated for OPG in the first year of life and for aqueductal stenosis at the age of 7 developed a PA of the right frontal lobe at the age of 11 and underwent thermal ablation (LITT procedure) of this lesion. Although the long-term effects of laser ablation in patients with NF1 are not yet known, this technique is more precise, less invasive, does not involve ionizing radiations in terms of volume of tissue ablation compared to other methods, and allows complete resection, avoiding collateral damage [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…LITT has also been advocated for newly diagnosed and recurrent pediatric brain tumors [136]. LITT-treated pathologies include: pilocytic astrocytomas [136][137][138], ependymomas [77,103,139], medulloblastomas [136,138], choroid plexus xanthogranulomas [136,138], subependymal giant cell astrocytomas [136,138,[140][141][142], gangliogliomas [136,138,143], neuroectodermal tumors [77,103,144], gliosis [143], RN [143] and hypothalamic hamartomas [140]. Reported indications include deep-seated and recurrent, tumors [136,145].…”
Section: Pediatric Tumorsmentioning
confidence: 99%
“…In terms of image guidance, improvements in MRI coil design and developments in laser probe design will not only improve the flexibility of the treatment but also would expand the possibility to treat lesions with even more complex shapes and locations. For instance, novel designs in the laser tip could provide the possibility to treat tumors in sensitive structures such as the brainstem [69]. Furthermore, Hafez et al reported the first case with a staged ablation of a large left insular tumor in order to minimize the postoperative edema or vascular complications in this highly eloquent area [70].…”
Section: Current Perspectivesmentioning
confidence: 99%